Innovation accelerator to make portuguese parishes smarter - Vizela, Inês (2022)
Vizela, I., Costa, E., & Santos, V. (2020). Innovation accelerator to make portuguese parishes smarter. In M. Banat, & S. Paiva (Eds.), Smart Technologies for Smart Cities: EAI/Springer Innovations in Communication and Computing (pp. 3-21). (EAI/Springer Innovations in Communication and Computing). Springer. https://doi.org/10.1007/978-3-030-39986-3_1